(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Traditional research focusing on children has been carried out by collecting informationfrom the children’s parents, teachers, and other adults. Information acquired from thechildren themselves has been considered of secondary importance. As the number of studies focusing on children has increased, it is important to consider the children themselves as research subjects. This article investigates the following areas: (1) how to encourage 5 to 7 year-old children to talk, (2) how a researcher, as an adult, can understand the child’s world, and (3) how a researcher can free him/herself from the adult-centered perspective. This article clarifies the features of a method forchild interviewing, and demonstrates how vividly and easily Finnish daycare children (N = 29) are able to talk about their experiences in a research interview.